2009
DOI: 10.1001/jama.2009.1601
|View full text |Cite
|
Sign up to set email alerts
|

Statin Use and Risk of Gallstone Disease Followed by Cholecystectomy

Abstract: Context Gallstone disease is a leading cause of morbidity in western countries and carries a high economic burden. Statins decrease hepatic cholesterol biosynthesis and may therefore lower the risk of cholesterol gallstones by reducing the cholesterol concentration in the bile. Data on this association in humans are scarce. Objective To study the association between the use of statins, fibrates, or other lipidlowering agents and the risk of incident gallstone disease followed by cholecystectomy. Design, Settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
87
1
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 40 publications
5
87
1
1
Order By: Relevance
“…Epidemiological studies have demonstrated that longterm oral therapy with statins reduces the risk of symptomatic gallstones disease [7,8]. Recent articles have proposed the therapeutic use of statins for the medical treatment of cholesterol gallstones [14].…”
Section: Expert Opinionmentioning
confidence: 99%
See 3 more Smart Citations
“…Epidemiological studies have demonstrated that longterm oral therapy with statins reduces the risk of symptomatic gallstones disease [7,8]. Recent articles have proposed the therapeutic use of statins for the medical treatment of cholesterol gallstones [14].…”
Section: Expert Opinionmentioning
confidence: 99%
“…Recent epidemiological studies have reported that patients with long-term statin use have a reduced risk of gallstones disease followed by cholecystectomy [8]. This effect was statistically evident among current statin users with five or more prescriptions (1 --2 years of statin use) or among former statin users with 20 or more prescriptions [7,8].…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…Human studies have shown potential benefit of statins in treating cholesterol gallstones [2,3]. A summary of the mechanisms involved have been reviewed by Ahmed et al [4].…”
mentioning
confidence: 99%